Identification of a mutation in the gene encoding the alpha subunit of the stimulatory G protein of adenylyl cyclase in McCune-Albright syndrome. - Schwindinger, W F (1992)
McCune-Albright syndrome (MAS) is characterized by polyostotic fibrous dysplasia, café-au-lait lesions, and a variety of endocrine disorders, including precocious puberty, hyperthyroidism, hypercortisolism, growth hormone excess, and hyperprolactinemia. The diverse metabolic abnormalities seen in MAS share the involvement of cells that respond to extracellular signals through activation of the hormone-sensitive adenylyl cyclase system (EC 4.6.1.1). Mutations that lead to constitutive activation of Gs alpha, the guanine nucleotide-binding regulatory protein that stimulates adenylyl cyclase activity, have been identified in a subset of human growth hormone-secreting pituitary tumors and human thyroid tumors. We report here the identification of a mutation in the gene encoding Gs alpha in a patient with MAS. Denaturing gradient gel electrophoresis was used to analyze amplified DNA fragments including exon 8 or exon 9 of the Gs alpha gene. In one subject with MAS a G-to-A transition was found in exon 8 of one of the two alleles encoding Gs alpha. This single-base substitution results in the replacement of arginine by histidine at position 201 of the mature Gs alpha protein. Semiquantitative analysis of amplified DNA indicated that the mutant allele was less prevalent than the wild-type allele in peripheral leukocytes and was present in very low levels in skin. These findings support the previous contention that the segmental distribution and variable expression of the cutaneous, skeletal, and endocrine manifestations of MAS reflect an underlying somatic mosaicism. Further, these results suggest that the molecular basis of MAS is a postzygotic mutation in Gs alpha that causes constitutive activation of adenylyl cyclase.